Assessing Social Entrepreneurship in Chile: Factors Involved in the Definition of Social Enterprises - Marfan Lineros, Carolina Ximena (2013)
Chile is right in the limit of between being an emerging and a developed country. Chile has recently entered to the OECD, has an unemployment rate of 6,2%, but has one of the worst income distribution indexes in Latin America. There is unrest in the population regarding public education, transport and health because of their lack of quality. In this scenario, and while NGOs have been around for long, the term ‘social entrepreneurship’ has only been used in Chile for less than 5 years. In spite of this, a blooming of for-profit social enterprises has marked the last 2 or 3 years. This dissertation attempts to provide empirical data using Townsend and Hart’s (2008) model for determining the organisational form of a social entrepreneurship venture as it explores the social entrepreneurship environment Chile, identifying opportunities and barriers for the development of this kind of venture. Six semi-structured interviews to key participants in the decision-making process that defined the organisational form in different cases were conducted through Skype from 7 July 2013 to 17 August 2013, running an average of 41 minutes. The cases had to comply with the following: have a social mission, be located in Chile, founded within the last 5 years, be currently operating, and have different operating fields than the rest. The cases were classified as forprofit or non-profit social ventures. Additionally, mission statements were analysed in order to obtain the organisation’s orientation. The results show that the organisational form of a social venture may be influenced in the first place by the founders’ goals. However, an organisational identity approach might be preferable. Social norm enabling the legitimacy of such ventures is another determining factor. Evidence seems to show that it is at least more important than any other external factor. Other factors determining the organisations’ form are, to a lesser degree, resource acquisition and the newness of the model implemented. Formal legitimacy is not considered an issue, given the flexibility of the Chilean laws. Associations and networks of social entrepreneurs contribute to the legitimacy of social entrepreneurship by making the concept more present in the collective conscious, contributing twofold: by fostering participation of individual entrepreneurs in new ventures, and by changing the norm on what is viewed on as ‘acceptable’ in the social and business world.